Synergistic Effect of Feeding Time and Diet on Hepatic Steatosis and Gene Expression in Male Wistar Rats. (31st May 2020) - Oosterman, Johanneke E.; Koekkoek, Laura L.; Foppen, Ewout; Unmehopa, Unga A.; Eggels, Leslie; Verheij, Joanne; Fliers, Eric; la Fleur, Susanne E.; Kalsbeek, Andries
Abstract : Objective: Eating out of phase with the endogenous biological clock alters clock and metabolic gene expression in rodents and can induce obesity and type 2 diabetes mellitus. Diet composition can also affect clock gene expression. This study assessed the combined effect of diet composition and feeding time on (1) body composition, (2) energy balance, and (3) circadian expression of hepatic clock and metabolic genes. Methods: Male Wistar rats were fed a chow or a free‐choice high‐fat, high‐sugar (fcHFHS) diet, either ad libitum or with food access restricted to either the light or dark period. Body weight, adiposity, and hepatic fat accumulation as well as hepatic clock and metabolic mRNA expression were measured after 5 weeks of the diet. Energy expenditure was measured using calorimetric cages. Results: Animals with access to the fcHFHS diet only during the light period showed more hepatic fat accumulation than fcHFHS dark‐fed animals despite less calories consumed. In contrast, within the chow‐fed groups, light‐fed animals showed the lowest hepatic fat content, but they also showed the lowest caloric intake. Locomotor activity and heat production followed feeding times, except in the fcHFHS light‐fed group. Hepatic clock and metabolic gene expression rhythms also followed timing of food intake. Yet, in the fcHFHS light‐fed animals, clock gene expression appeared 3 hours advanced compared with chow light‐fed animals, an effect not observed in the fcHFHS dark‐fed animals. Conclusions: An fcHFHS diet consumed in the light period promotes hepatic fat accumulation and advances clock gene expression in male Wistar rats, likely because of a mismatch between energy intake and expenditure.